2013
DOI: 10.5944/educxx1.16.1.728
|View full text |Cite
|
Sign up to set email alerts
|

Actitud, Presión Social Y Educación Inclusiva en Aulas Con Diversidad Lingüística Y Cultural (Attitudes, Social Pressure and Inclusive Education in Classrooms With Cultural and Linguistic Diversity)

Abstract: RESUMENSe estudiaron las actitudes lingüísticas del alumnado de E.S.O. en Cataluña, desde un enfoque que tuviera en cuenta la presión social. Se pretendía analizar la posibilidad de realizar intervenciones educativas inclusivas, la relación entre actitudes lingüísticas y competencia y las posibles variables explicativas de dichas actitudes. Se aplicó a 1206 escolares de 2º y 4º de E.S.O. un cuestionario que evaluaba actitudes lingüísticas y condición lingüística familiar, recabando edad de llegada y tiempo de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 20 publications
3
20
1
3
Order By: Relevance
“…Positive attitudes towards Catalan were more present in the case of students with a length of residence of more than six years, who were born in the host society or immigrated before the age of ten, or who started schooling in Catalonia. These findings were confirmed by Madariaga, Huguet, and Lapresta (2013), who investigated 1206 autochthonous and immigrant secondary education students and also found that their attitudes were influenced by area of origin, home language, length of residence, age of arrival, and place of birth.…”
Section: The Socio-linguistic and Educational Context Of Cataloniamentioning
confidence: 53%
See 2 more Smart Citations
“…Positive attitudes towards Catalan were more present in the case of students with a length of residence of more than six years, who were born in the host society or immigrated before the age of ten, or who started schooling in Catalonia. These findings were confirmed by Madariaga, Huguet, and Lapresta (2013), who investigated 1206 autochthonous and immigrant secondary education students and also found that their attitudes were influenced by area of origin, home language, length of residence, age of arrival, and place of birth.…”
Section: The Socio-linguistic and Educational Context Of Cataloniamentioning
confidence: 53%
“…The attitude questionnaire selected has been successfully used in Catalonia (Navarro and Huguet 2005;Huguet, Janés, and Chireac 2008;Madariaga, Huguet, and Lapresta 2013). The instrument follows the model of the one constructed by Sharp et al (1973) and it was adapted to the Catalan context by the Catalan Education Service ('Servei d'Ensenyament del Català' -SEDEC) and then readapted to the current characteristics of the secondary education student population, taking into account the immigrant group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lenguas de instrucción. La construcción de una identidad colectiva no excluyente supone tener en cuenta la lengua y cultura de la población inmigrante (Madariaga et al, 2013) así como las lenguas minoritarias o cooficiales de cada país (Vez, 2009). Los valores compartidos por las diversas culturas, valores transculturales, son relevantes educativamente como agentes promotores de cohesión social (Ibáñez-Martín et.…”
Section: Indicadores De Equidadunclassified
“…Together with these elements, other factors have been identified as key agents in the formation process of language attitudes. The place of birth is one of the variables reported to affect language attitudes of local and immigrant population, as empirical data confirm that autochthonous and immigrant students have different attitudinal patterns, with the former usually favouring Catalan and the latter Spanish (Bernaus et al 2004;Lapresta et al 2009;Janés 2010, 2016;Madariaga, Huguet, and Lapresta 2013;Rojo, Madariaga, and Huguet 2010). However, this view has been contested by studies emphasizing the wide variety of language attitudes in Age has also been identified as a modified element, and studies have concluded that language attitudes can change with the age (Baker 1992;Bernaus, Moore, and Cordeiro 2007;Dörnyei and Csizér 2002;Heining-Boynton and Haitema 2007).…”
mentioning
confidence: 99%